Excavations in Residential Areas of Tikal--Nonelite Groups Without Shrines : Tikal Report 20A - Haviland, William A. (Book collections on Project MUSE., 2014)
Excavations in Residential Areas of Tikal--Nonelite Groups Without Shrines is a two-volume presentation of the excavations carried out in and near small residential structures at Tikal, Guatemala. Tikal Report 20A is a descriptive presentation of the excavation data and includes nearly two hundred illustrations.